The Effect of Price, Product Quality, and Promotion on The Purchasing Decision of MS Glow Products at MS Glow Tulungagung Branch Agent - Dinandra Faidatul Buduri; Muhammad Alhada Fuadilah Habib (Universitas Islam Darul Ulum Lamongan, 2023)
Ms Glow is a beauty skincare manufacturer that has many agents spread throughout Indonesia. In the midst of lots of competition with similar products, Ms Glow managed to score high sales on the Shopee marketplace. This study aims to determine the effect of price, product quality, and promotion partially and simultaneously on purchasing decisions for Ms Glow's products at Ms Glow's Tulungagung branch. Theoretically, there are various factors that can influence the decision to purchase Ms Glow products including price, product quality, and promotions. The population in this study were consumers of Ms Glow Ngantru's products, which were taken using non-probability sampling with an accidental technique. Samples were taken using the Slovin formula at a 95% confidence level so that a total sample of 95 respondents was obtained. Data collection was carried out using a questionnaire. The analytical method used in this study is multiple linear regression analysis with the help of the SPSS version 26 program. Hypothesis testing uses the t test and simultaneously with the f test. The results of this study indicate that partially price, product quality, and promotions have a positive and significant effect on purchasing decisions for Ms Glow's products at the Ms Glow agent Tulungagung branch. Whereas the simultaneous test shows that price, product quality, and promotions simultaneously have a positive and significant effect on the decision to purchase Ms Glow's products at the Ms Glow agent Tulungagung branch.